Processes of Imaging and Imagining: Toward a Pragmatic Clarification of the Image - Colapietro, Vincent (Recherches sémiotiques / Semiotic Inquiry, 2013)
The paper aims at a pragmatist clarification of imaging and imagining. Using Peirce’s doctrine of the three grades of conceptual clarification (tacit familiarity, abstract definition, and pragmatic elucidation), the author tries to clarify our processes and practices of imaging and imagining by considering them in light of these distinct levels. Above all, he endeavors to push the discussion from the level of abstract definition to that of pragmatic clarification, thereby focusing on the habits of agents in situ, not simply verbal formulations offered in the abstract. Borrowing from Barbara Bolt, he uses as one of his examples that of an artist “working hot”. A process wherein conscious intentions and unconscious drives, cognitive designs and thick materiality, conspire to embody themselves in perceptible media is one especially worthy of examination. Hence, from an overview of Peirce’s general theory of signs, the author turns to some of the specific uses of that theory, uses not central to Peirce’s own interests. Artistic production and performance are foremost among these uses. These are, after all, ones in which the dynamics of imaging and imagining are often more vividly on display than elsewhere.